Pengaruh Kepuasan Kerja Dan Pemberian Kompensasi Non Finansial Terhadap Kinerja Individual Pada Pekerja Gen Z - Ni’matul Khoiriyah; Sasmita Mardianingrum; Siti Maslichah; Nafia Ilhama Qurratu'aini (Master Manajemen, 2025)
The aim of this research is to analyze the relationship between job satisfaction, non-financial compensation and individual performance in the working Gen Z population. The method used is a quantitative method, using a purposive sampling technique based on 40 working generations of Gen Z. Data collection was carried out by distributing questionnaires online via the WhatsApp application. The results of this research show that job satisfaction has a positive and insignificant effect on individual performance and non-financial benefits have a negative and insignificant effect on individual performance.